KAJIAN EFEK RESIDU AMELIORAN IN SITU BATUBARA BITUMINOUS DAN LAPISAN PENGOTORNYA TERHADAP SIFAT FISIKA-KIMIA TANAH REKLAMASI TAMBANG BATUBARA DAN HASIL KEDELAI - Sunarti; Khairul, Khairul; Ajidirman (Akta Agrosia, 2022)
Application of slow decomposed organic ameliorants is expected to have a long-term impact on improving soil Physico-chemical properties. The source of in situ organic carbon that is easy to obtain on coal mine reclamation land are the coal itself and its coal impurities (parting) ameliorants. They are slow to decompose, so the residue can last for a long time in the soil. This study aimed to examine the effect of first-year residue of both coal and parting as ameliorants on the improvement of the physical and chemical properties of coal mine reclaimed soil and soybean yields. A pot study was เว็บสล็อต | R4shub conducted using a randomized block design with 3 treatments. The treatments tested were residues from the first year of the administration of ameliorant in situ, namely: Control, Bituminous coal ameliorant residue, and parting. Both coal and parting were tested with 5 doses each consisting of 5, 10, 15, 20, or 25 tons ha-1. The results showed that the first-year residue of bituminous coal ameliorant and coal impurities significantly affected some of the chemical properties of coal mine reclaimed soil. Both types of ameliorant residues had a very significant effect on increasing C-organic, humic acid, and total N content. The highest increase in soil organic C was found in soil ameliorated by using bituminous coal residues at 25 tons ha-1, and those by using coal impurities at was 20 tons ha-1. However, treatments did not affect soybean growth and yield.